Modelling production cost scenarios for biofuels and fossil fuels in Europe - Gunter Festel; Martin Würmseher; Christian Rammer; Eckhard Boles; Martin Bellof (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This paper presents the results of a calculation model for biofuel production costs in 2015 and 2020 based on raw material price projections and considering scale and learning effects. Distinguishing six types of biofuels, the paper finds that scale economies and learning effects are critical for 2nd generation biofuels to become competitive. In case these effects can be utilized, cost saving potentials for 2nd generation biofuels are significant.
urn:nbn:de:bsz:180-madoc-347901
Keywords: L25; L26; J24; 330; Biofuels; Production Cost Scenarios; Raw Material Price Projection; Conversion Costs